2013
DOI: 10.1038/nmeth.2361
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic and tunable human gene activation by combinations of synthetic transcription factors

Abstract: Mammalian genes are regulated by the cooperative and synergistic actions of many transcription factors. In this study we recapitulate this complex regulation in human cells by targeting endogenous gene promoters, including regions of closed chromatin upstream of silenced genes, with combinations of engineered transcription activator–like effectors (TALEs). These combinations of TALE transcription factors induced substantial gene activation and allowed tuning of gene expression levels that will broadly enable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
236
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(252 citation statements)
references
References 25 publications
13
236
0
Order By: Relevance
“…Although nucleosome occlusion will prevent the binding of some TALEs, the data we present here suggest that in the absence of such occlusion, TALEs can bind to repressed chromatin at least in some cells in the population. Together with the recent report that TALEs synergise to perform their function, our data reinforce the idea that using a series of TALEs with adjacent binding sites [23,24] is likely to increase the chances of TALE proteins being effective in vivo. Southern blots to determine nucleosome positioning.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Although nucleosome occlusion will prevent the binding of some TALEs, the data we present here suggest that in the absence of such occlusion, TALEs can bind to repressed chromatin at least in some cells in the population. Together with the recent report that TALEs synergise to perform their function, our data reinforce the idea that using a series of TALEs with adjacent binding sites [23,24] is likely to increase the chances of TALE proteins being effective in vivo. Southern blots to determine nucleosome positioning.…”
Section: Discussionsupporting
confidence: 87%
“…Instead, we find that there is a relatively small difference in binding to active and repressed loci, implying that TALEs should function at inactive loci. Consistent with this, TALEs were recently shown to function at such loci [23].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Like zinc fingers, TALEs are also compatible with numerous epigenetic modifiers, including the TET1 hydroxylase catalytic domain (Maeder et al 2013b) and the lysine-specific histone demethylase 1 (LSD1) (Mendenhall et al 2013) domains, which have been used for targeted CpG demethylation and histone demethylation, respectively. In particular, the ease with which a large number of TALEs can be constructed has enabled the discovery that tiling a promoter sequence with combinations of synthetic transcription factors can lead to a synergistic increase in gene expression (Maeder et al 2013b;Perez-Pinera et al 2013). And, like zinc fingers (Beerli et al 2000b;Pollock et al 2002;Magnenat et al 2008;Polstein and Gersbach 2012), TALE activators have also been successfully engineered to regulate gene expression in response to external or endogenous ) chemical stimuli, optical signals , and even proteolytic cues (Copeland et al 2016;Lonzaric et al 2016).…”
Section: Targeted Transcription Factors Tools For Modulating Gene Expmentioning
confidence: 99%
“…Recent studies have demonstrated that the nucleasenull Cas9 (dCas9), which was fused with transcription activation domains (e.g. VP16 or VP64), functioned as a transcriptional activator [8]- [18] , suggesting that the CRISPR/Cas9-based system can be used to control the expression of specific genes. Since the transcriptional activity of the dCas9 activators was not high [8], [16] , however, the efficacy of the cell-fate changes was still very low (~10%) [17] .…”
mentioning
confidence: 99%